2018
DOI: 10.4081/ejh.2018.2942
|View full text |Cite
|
Sign up to set email alerts
|

Expression of acetylated tubulin in the postnatal developing mouse cochlea

Abstract: Microtubules are an essential component of the cytoskeleton of a eukaryotic cell. The post-translational tubulin modifications play an important role in regulating microtubule properties, acetylation tubulin is one of the major post-translational modifications of microtubules. Acetylation tubulin has also been shown to be expressed in the cochlea. However, the detailed expression profiles of acetylation tubulin protein during development have not yet been investigated in the postnatal mammalian cochlea. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
(31 reference statements)
5
11
0
Order By: Relevance
“…In the zebrafish model, the inhibition of this enzyme leads to developmental defects such as shortening of the body, neuromuscular defects, or reduction of eye and head size (Akella et al, 2010). Furthermore, abundant numbers of acetylated microtubules were reported in the cochlea in pillar and Deiter's cells (Li and Yang, 2015;Szarama et al, 2012;Tannenbaum and Slepecky, 1997) as observed in our immunofluorescence labeling for acetylated tubulin, and ATAT1 as the enzyme responsible for the acetylation of the tubulin in mice (Kalebic et al, 2013;Liu et al, 2018;Shida et al, 2010). We observed the disappearance of the acetylated microtubules in the pillar cells of the Atat1 KO mice, confirming the hypothesis that this enzyme is responsible of the acetylation of the microtubules present in pillar cells.…”
Section: -Protofilament Microtubules In Mammalian Earssupporting
confidence: 53%
“…In the zebrafish model, the inhibition of this enzyme leads to developmental defects such as shortening of the body, neuromuscular defects, or reduction of eye and head size (Akella et al, 2010). Furthermore, abundant numbers of acetylated microtubules were reported in the cochlea in pillar and Deiter's cells (Li and Yang, 2015;Szarama et al, 2012;Tannenbaum and Slepecky, 1997) as observed in our immunofluorescence labeling for acetylated tubulin, and ATAT1 as the enzyme responsible for the acetylation of the tubulin in mice (Kalebic et al, 2013;Liu et al, 2018;Shida et al, 2010). We observed the disappearance of the acetylated microtubules in the pillar cells of the Atat1 KO mice, confirming the hypothesis that this enzyme is responsible of the acetylation of the microtubules present in pillar cells.…”
Section: -Protofilament Microtubules In Mammalian Earssupporting
confidence: 53%
“…Since these regional distinctions could also be indicative of lineage restrictions, the identification of markers that define each domain could be utilized to create gene therapy targeting vectors specific for medial or lateral SC types (Stone and Cotanche, 2007;Cox et al, 2014). Comparison to existing adult SC (Liu W. J. et al, 2018;Ranum et al, 2019) and HC (Liu H. et al, 2014;Ranum et al, 2019) datasets has been provided as Supplementary Figures S14-S24 (Supplemental Datasheet S2).…”
Section: Adult Cochlear Supporting Cells Can Be Categorized Into Two mentioning
confidence: 99%
“…Hair cell stereocilia, which are essential for hair cell mechano-transduction ( Fettiplace and Hackney, 2006 ), also showed gradual elongation during organoid differentiation ( Figures 1 J–1L). Importantly, the kinocilia, developmental structures present in immature but not mature cochlear hair cells ( Liu et al., 2018b ), were gradually lost by DIV24 and DIV26 ( Figures 1 J, 1K, and 1M). These findings indicate that expansion and differentiation of the cochlear organoids is highly efficient, and hair cells differentiated within the organoids show developmental maturation.…”
Section: Resultsmentioning
confidence: 99%